2013
DOI: 10.1371/journal.ppat.1003632
|View full text |Cite|
|
Sign up to set email alerts
|

ISG15 Regulates Peritoneal Macrophages Functionality against Viral Infection

Abstract: Upon viral infection, the production of type I interferon (IFN) and the subsequent upregulation of IFN stimulated genes (ISGs) generate an antiviral state with an important role in the activation of innate and adaptive host immune responses. The ubiquitin-like protein (UBL) ISG15 is a critical IFN-induced antiviral molecule that protects against several viral infections, but the mechanism by which ISG15 exerts its antiviral function is not completely understood. Here, we report that ISG15 plays an important ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 53 publications
3
43
0
1
Order By: Relevance
“…Recently, we reported that the phagocytic capacity of macrophages is highly regulated by IFN (35). Latex beads are a common substrate used in biochemical studies to study phagocytosis in macrophages (28).…”
Section: Attenuated and Nonattenuated Poxvirus Vectors Induce Cpe In mentioning
confidence: 99%
“…Recently, we reported that the phagocytic capacity of macrophages is highly regulated by IFN (35). Latex beads are a common substrate used in biochemical studies to study phagocytosis in macrophages (28).…”
Section: Attenuated and Nonattenuated Poxvirus Vectors Induce Cpe In mentioning
confidence: 99%
“…Appreciating that other pathways may also be modulated by ISG15, we are currently investigating whether the AKT-PI3K and mTOR/S6K pathways, both of which have been shown to be important in PDAC (44,45), are also affected by free ISG15. Along these lines, previous work from our laboratory has shown a direct link between AKT signaling and ISG15 in macrophages (11). We have reported that ISG15 plays an important role in the regulation of macrophage functions as ISG15 À/À macrophages display reduced activation, phagocytic capacity, and programmed cell death activation in response to vaccinia virus infection.…”
Section: Discussionmentioning
confidence: 67%
“…Since its discovery in 1979 (10), ISG15 has been extensively studied as an anti-viral protein (11)(12)(13), but we now appreciate that ISG15 has many other functions, including ISGylation, a ubiquitinlike modification process whereby ISG15 can be covalently linked to cytoplasmic and nuclear proteins (14). Like ubiquitin, ISG15 coupling to target proteins involves the ISG15-specific E1-like activating enzyme (UbE1L), the conjugating E2 enzyme, and the ligating E3 enzymes (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is important to underscore that free ISG15 becomes secreted and the lack of secreted ISG15 is associated with severe mycobacterial disease in both mice and humans (37). Furthermore, we recently reported the importance of ISG15 in regulating macrophage activity (38), indicating that ISG15 is a crucial molecule in the regulation of the immune response. Additional studies to understand the biological functions of unconjugated intracellular and/or extracellular ISG15 and of ISGylation may help our knowledge of innate immunity and on how viruses have developed strategies to subvert it.…”
Section: (D) Isg15mentioning
confidence: 99%